2015
DOI: 10.1016/j.atmosenv.2014.08.072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of operational online-coupled regional air quality models over Europe and North America in the context of AQMEII phase 2. Part II: Particulate matter

Abstract: The second phase of the Air Quality Model Evaluation International Initiative (AQMEII) brought together sixteen modeling groups from Europe and North America, running eight operational online-coupled air quality models over Europe and North America on common emissions and boundary conditions. With the advent of online-coupled models providing new capability to quantify the effects of feedback processes, the main aim of this study is to compare the response of coupled air quality models to simulate levels of O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
105
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 75 publications
18
105
0
Order By: Relevance
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 76%
See 1 more Smart Citation
“…This is comparable with other models (Im et al, 2015). However, short periods with strong overestimations of [NO − 3 ] were also observed in previous New scheme (this study) 50 % * * Suggested by Sintermann et al (2012), Backes et al (2016), and Chen et al (2016b). studies.…”
Section: Improvement Of the Particulate Nitrate Predictionsupporting
confidence: 76%
“…In previous evaluation studies (Im et al, 2015;Wolke et al, 2012), the COSMO-MUSCAT model predicted particulate nitrate mass concentrations ([NO − 3 ]) in fair agreement with the measurements, with an overestimation in the range of 50 % on long-term average. This is comparable with other models (Im et al, 2015).…”
Section: Improvement Of the Particulate Nitrate Predictionmentioning
confidence: 91%
“…During the second phase of the Air Quality Model Evaluation International Initiative (AQMEII), the nine working groups using the Weather Research and Forecasting model coupled with chemistry (WRF-Chem) operationally reported an overall underestimation of the annual surface ozone (O 3 ) levels reaching up to 18 % over Europe and 22 % over North America (Im et al, 2015b) with autumn overestimation and winter underestimation. The meteorological and chemical configurations of the different groups were found to have a considerable effect on simulated O 3 levels.…”
Section: G K Georgiou Et Al: Summer Eastern Mediterranean Air Qualmentioning
confidence: 99%
“…Several studies of available observations show that the PM 10 European Union air quality standard (50 µg m −3 , daily average) is exceeded at many locations around the basin because of a combination of mineral dust and anthropogenic pollutants from local sources (Gerasopoulos et al, 2006;Gobbi et al, 2007;Koçak et al, 2007;Rodriguez et al, 2007;Kaskaoutis et al, 2008). Mineral dust outbreaks, although transported through the Mediterranean sea during all seasons, are more frequent in spring and summer, where dust plumes are transported through the Atlantic and reach mainly and regularly the western part of the region (Moulin et al, 1998;Israelevich et al, 2012;Salvador et al, 2014;Ripoll et al, 2015). In summer, mineral dust aerosols are also observed over central Europe (Israelevich et al, 2012;Salvador et al, 2014).…”
Section: Introductionmentioning
confidence: 99%